Genetic control of the eighth component of complement. - D Raum; M A Spence; D Balavitch; S Tideman; A D Merritt; R T Taggart; B H Petersen; N K Day; C A Alper (The Journal of Clinical Investigation, 1979)
Using isoelectric focusing in polyacrylamide gel and a hemolytic assay for development of patterns, extensive, structural polymorphism in human C8 has been delineated. Two alleles, C8A and C8B, have been identified in orientals, with gene frequencies of 0.655 and 0.345. In blacks, what appears to be a third common allele was found, so that frequencies were 0.692, 0.259, and 0.049 for C8A, C8B, and C8A1. In whites, C8A1 was rare with a frequency of 0.003, and frequencies for C8A and C8B were 0.649 and 0.349. Inheritance was autosomal codominant in family studies and the distribution of types in random unrelated populations fit the Hardy-Weinberg equilibrium in all groups. C8 allotypes have been determined for two previously studied families, each with a homozygous C8-deficient propositus. This study suggests that C8 deficiency is a silent or null allele of the C8 structural locus, and that half normal levels of C8 cannot be used as a single criterion for the establishment of heterozygous C8 deficiency. C8 allotypes, as well as 18 other autosomal markers, were also determined for 24 families. The C8 structural locus is not closely linked to these markers, including the human histocompatibility loci complex. Images